Pelatihan Pembuatan Hand Sanitizer Berbahan Baku Toga bagi Masyarakat Pedesaan - Hendratno Hendratno; Suryanti Suryanti; Heru Subrata; Neni Mariana; Wiryanto Wiryanto (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING ON MAKING HAND SANITIZER OF TOGA RAW MATERIAL FOR RURAL COMMUNITIES. The target of this activity is to educate the public to live healthily by realizing the potential in their surroundings. With the existence of Covid-19, it is hoped that rural communities will care more about the environment by caring for and making maximum use of available resources. The purpose of PKM activities is to empower rural communities in order to produce hand sanitizers that can be used for themselves, their families, and if possible, for economic benefits and produce products that have a sale value. Hand sanitizers are cleaning fluids used to wash hands that contain natural substances that can reduce the risk of attaching germs, bacteria, or viruses to a person’s body. With consistent use. This cleaning fluid can at least prevent the infection/disease due to the lack of cleanliness of a person’s body (especially the hands). Through independent production the community is expected to benefit economically. This will be able to support the economy of rural communities who are currently experiencing many problems, for example, people who are unemployed, merchandise that are not selling well, and other dire situations. The training methods used are lectures, tutorials, and hands-on methods to produce hand sanitizers from the materials around them, for example betel and aloe vera plants which are often found in rural communities. The material being trained is how to make hand sanitizers made from toga in the surrounding environment.